Unveiling the Obstacles: Tackling Challenges in Public Basic School Management in Nigeria - Moses Adeleke Adeoye; Rasheedat Modupe Oladimeji; Jubril Olaniyi Ayuba; Yusuff Olatunji Abimbowo (Mimbar Pendidikan Indonesia, 2024)
The management of public basic schools in Nigeria gives a myriad of challenges that hinder the effective delivery of education. This study aims to identify and examine those obstacles, offering insights into capability solutions to improve the management of public basic schools within the country. Addressing the demanding situations in public basic school management in Nigeria calls for a multifaceted method that encompasses infrastructure development, resource allocation, administrative reforms, and curriculum upgrades. By tackling those barriers, stakeholders can work closer to developing an academic environment that fosters holistic improvement, empowers educators, and equips learners with the capabilities and realise the way to thrive within the 21st century. Through a complete overview of existing literature, the study sheds mild on the important challenges confronted by school administrators, teachers, and other stakeholders. By understanding these obstacles, policymakers and educators can increase focused strategies to enhance the exceptional of education and ensure the holistic improvement of learners in Nigeria.